Analysis of Situational Leadership and Financial Compensation on Employee Performance Mediated by Motivation - Filzah, Razita Sabrina; Susila, Ihwan (Yayasan Riset dan Pengembangan Intelektual, 2025)
This study aims to investigate the effects of situational leadership and financial compensation on employee performance, with motivation as a mediating variable. A quantitative approach was employed, using structured questionnaires distributed to employees at dealerships in the Soloraya area. The sample was selected purposively based on criteria such as employment status, age (21–35), and residence, yielding at least 50 respondents. Data were analyzed using Partial Least Squares (PLS) in SmartPLS 4.0, including assessments of validity, reliability, multicollinearity, and structural relationships through R², Q², t-tests, and path coefficients. The results indicate that situational leadership positively and significantly influences motivation, while financial compensation positively and significantly affects both employee performance and motivation. However, motivation does not significantly impact employee performance and cannot mediate the effects of situational leadership or financial compensation. These findings suggest that organizations should focus directly on leadership practices and compensation structures to enhance performance. Future research may explore additional variables, broader geographic contexts, or qualitative methods for deeper insight into the interplay between leadership, compensation, motivation, and performance.